2021
DOI: 10.3390/e23081049
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Identification Systems with Noisy Enrollment for Gaussian Sources and Channels

Abstract: In the present paper, we investigate the fundamental trade-off of identification, secret-key, storage, and privacy-leakage rates in biometric identification systems for remote or hidden Gaussian sources. We use a technique of converting the system to one where the data flow is in one-way direction to derive the capacity region of these rates. Also, we provide numerical calculations of three different examples for the system. The numerical results imply that it seems hard to achieve both high secret-key and sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Also, it was demonstrated that the strong secrecy for secrecy-leakage of SKA systems is achievable by information-spectrum methods [22]. For future work, we plan to clarify the optimal tradeoff for GS and CS models with noisy enrollment as in [24], [25] and vector Gaussian sources as in [26].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was demonstrated that the strong secrecy for secrecy-leakage of SKA systems is achievable by information-spectrum methods [22]. For future work, we plan to clarify the optimal tradeoff for GS and CS models with noisy enrollment as in [24], [25] and vector Gaussian sources as in [26].…”
Section: Discussionmentioning
confidence: 99%
“…where ⊕ k denotes the addition modulo-|P k | defined in (43). The helper data j k is shared with the CEO for reconstructing the source signal.…”
Section: Agents (Encoding)mentioning
confidence: 99%
“…Proof: The above lemma follows by the fact that the latter half of the helper data, i.e., S k ⊕ k P k , leaks no information about the source identifiers since the index S k is completely masked by the private key P k . The readers may refer to the analysis of privacy leakage in [5], [43] for a detailed discussion.…”
Section: Lemma 1 It Holds Thatmentioning
confidence: 99%
“…A plethora of human anatomical features have been used for biometric systems. As presented in Figure 1, some of these include the use of fingerprints, face, iris, retina, voice, handwritten, face thermogram, hand geometry recognition, palm vein, and DNA matching [2]- [15]. In facial recognition systems (Fig.…”
Section: Introductionmentioning
confidence: 99%